2021
DOI: 10.3390/jcm10143142
|View full text |Cite
|
Sign up to set email alerts
|

History of IgA Nephropathy Mouse Models

Abstract: IgA nephropathy (IgAN) is the most common primary glomerulonephritis in the world. It was first described in 1968 by Jean Berger and Nicole Hinglais as the presence of intercapillary deposits of IgA. Despite this simple description, patients with IgAN may present very broad clinical features ranging from the isolated presence of IgA in the mesangium without clinical or biological manifestations to rapidly progressive kidney failure. These features are associated with a variety of histological lesions, from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Increasing evidence has indicated the importance of the gut-kidney axis in IgA nephropathy. The existing experimental model provides scattered clues [32]. For example, α1KI mice showed increased IgA polymerization levels when they were transferred from a germ-free to a conventional immune stimulation condition [33].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated the importance of the gut-kidney axis in IgA nephropathy. The existing experimental model provides scattered clues [32]. For example, α1KI mice showed increased IgA polymerization levels when they were transferred from a germ-free to a conventional immune stimulation condition [33].…”
Section: Discussionmentioning
confidence: 99%
“…The amplicon pools were prepared for sequencing, and the size and quantity of the amplicon library were assessed on an Agilent 2100 Bioanalyzer (Agilent, USA) and with the Library Quantification Kit for Illumina (Kapa Biosciences, Woburn, MA, USA), respectively. The libraries were sequenced on NovaSeq PE250 platform [11, 12].…”
Section: Methodsmentioning
confidence: 99%
“…The model of experimental IgAN was established by the immunity combination method of oral bovine serum albumin (BSA) (MedChemExpress, USA) administration and staphylococcal enterotoxin B (MedChemExpress, USA) injection [12][13][14]. In brief, pseudo-germfree mice (ABX mice) were randomly divided into four groups: the blank group (ABX 0 ), model group (half-dose immunity combination (ABX 1/2 ), 75% immunity combination (ABX 3/4 ), and full-dose immunity combination (ABX 1 ) group; each group included 6 animals.…”
Section: Animal Modelmentioning
confidence: 99%
“…It has been demonstrated that oxidative stress-induced protein oxidation and lipid peroxidation is one of the underlying pathogenic mechanisms [ 165 , 166 , 167 , 168 , 169 ]. While animal models of IgAN are available for studying the pathogenesis of IgAN and exploring therapeutic approaches [ 170 , 171 ], the potential effects of ALA in this kidney disorder have not been evaluated. Nonetheless, it is conceivable that ALA would exhibit nephroprotective effects in IgAN, given its powerful antioxidant capacity.…”
Section: Miscellaneousmentioning
confidence: 99%